Kajian Literatur: Analisis Pengaruh Suhu Dingin Ekstrem Terhadap Radang Dingin Pada Pekerja Tempat Penyimpanan Beku - Andi Abdillah; Ainun Tungga Dewi; Rubayat Indradi; Desy Andari (Puslitbang Sinergis Asa Professional, 2023)
Frostbite is a disease caused by continuous exposure to extreme cold and is very susceptible to cold storage workers. This paper focuses on the study of Frostbite due to exposure to cold temperatures in the cold storage room. This study uses a literature study method using search results through the research results library and a review of 30 references that have been presented in reputable international journals indexed by Scopus Q1, Q2 and Q3. Besides that, national journals indexed by Sinta and book references are also used. The results of this study indicate a relationship between an increase of temperature in the cold room with an increase in intercellular fluid in human body tissue to freeze due to extreme cold temperatures. The first phase of frostbite treatment is to remove the sufferer from the environment with extreme cold temperatures as soon as possible. Increasing body temperature from the inside (with food / drink / medicine) and the outside (warm water) is a good option for the first phase. In the second phase, sufferers need professional help in the medical field. Avoid breaking the clear liquid layer. The third and fourth phases require first aid to avoid secondary infection.